Prevalence of urinary incontinence in high-impact sports athletes and their association with knowledge, attitude and practice about this dysfunction - Brito Cardoso, A. M.; Oliveira de Paiva Lima, C. R.; Souto Ferreira, C. W. (European Journal of Sport Science, 2018)
Objective: To evaluate the prevalence of urinary incontinence (UI) in female athletes practising high-impact sports and its association with knowledge, attitude and practice (KAP).